Getting into secondary teaching - Davies, Andy; Norman, Mel (Critical learning., 2016)
Essential reading if you are considering making an application for secondary initial teacher education or preparing to begin your programme. Introduces you to a range of perspectives on teaching and teacher education and guides you through the application process to ensure you choose the training route that's right for you.